The Effect of the Human Development Index on Environmental Performance Index Measurement: A Maqāṣid al-Sharī’ah Perspective - Widodo, Prima Ariyo; Isman, Isman; Risdayani, Risdayani; Budiman, Mamdukh (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
This research aims to evaluate the improvement in the Human Development Index (HDI), which encompasses health, education, and income, between 2021 and 2023. Furthermore, this research analyses the relationship between the human development index and the environmental performance index from the perspective of Maqāṣid al-Shari’ah. Employing a mixed-methods approach, this study integrates qualitative and quantitative methodologies. The quantitative method uses linear regression for data analysis and interpretation with descriptive pattern qualitative analysis. The findings reveal a negative correlation between Indonesia's HDI and its EPI. Individuals with higher levels of education, better health, and increased income tend to exhibit greater awareness of environmental sustainability. This finding supports Maqāṣid al-Shari’ah, which emphasizes the importance of protecting life, education, property and offspring. Improving human welfare and protecting the environment are key to achieving sustainable development. Government policies should simultaneously promote human development and environmental protection. This fostered sustainable prosperity in line with the principles of Maqāṣid al-Shari’ah.